2015
DOI: 10.1116/1.4931622
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial structures for deep reactive ion etching of high-aspect ratio kinoform silicon x-ray lenses

Abstract: O. (2015). Sacrificial structures for deep reactive ion etching of high-aspect ratio kinoform silicon x-ray lenses. Journal of Vacuum Science and Technology. Part B. Microelectronics and Nanometer Structures, 33(6), [062001]. DOI: 10.1116/1.4931622 Sacrificial structures for deep reactive ion etching of high-aspect ratio kinoform silicon x-ray lenses This article describes the realization of complex high-aspect ratio silicon structures with feature dimensions from 100 lm to 100 nm by deep reactive ion etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…This variation must be reduced in the future, since it is significantly larger than the depth of focus (~1 mm [7]). A more accurate control of the sidewall profile can readily be achieved by means of a more extensive optimization of the etching process of the silicon master [23]. Although, in terms of economy, this will consume additional resources, it will be insignificant, not least because we expect that more than 1000 polymeric parts may be obtained from a single master [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation must be reduced in the future, since it is significantly larger than the depth of focus (~1 mm [7]). A more accurate control of the sidewall profile can readily be achieved by means of a more extensive optimization of the etching process of the silicon master [23]. Although, in terms of economy, this will consume additional resources, it will be insignificant, not least because we expect that more than 1000 polymeric parts may be obtained from a single master [27].…”
Section: Discussionmentioning
confidence: 99%
“…DRIE was a critical process step in ensuring the near-90° sidewalls required to guarantee both lens uniformity and the successful release of the polymeric part from the mold. To this end, we utilized sacrificial structures, which facilitated accurate profile control [23]. Optical profilometry confirmed that the etched sidewalls were slightly positively tapered by 0.5°, which favored a successful release of the injection molded polymeric part.…”
Section: Micro Fabricationmentioning
confidence: 99%
“…Si microstructures, such as pillar and hole arrays, can be prepared by photolithographically patterning photoresists (PRs) on surfaces and deep reactive-ion etching (DRIE). In particular, the Bosch process has been used to produce deep trenches during DRIE. , However, the DRIE process is expensive and passivation layers, such as C 4 H 8 , need to be coated along the side walls of the patterns to protect Si against lateral etching, which is undesirable for industrial applications. An alternative method of micromachining Si involves wet etching using an etchant such as TMAH (tetramethylammonium hydroxide) or a mixture solution of potassium hydroxide (KOH) and isopropyl alcohol (IPA), which enable the micromachining of bulk Si; however, etching directionality is highly restricted by the orientation of the Si crystal. , …”
Section: Introductionmentioning
confidence: 99%
“…Anisotropic etching of silicon using deep reactive ion etching (DRIE) is among the key technologies for fabrication of microstructures for a wide range of applications [1,2,3]. DRIE processes are often based on the cyclic Bosch process [4].…”
Section: Introductionmentioning
confidence: 99%